BENTUK PERJANJIAN SEWA MENYEWA RUMAH TOKO (RUKO) ANTARA PENYEWA RUKO DENGAN PEMILIK RUKO DI KOTA DENPASAR - Pradantya Adhi Wibawa, A. A. Gde; Sukihana, Ida Ayu; Sri Indrawati, A. A. (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Leasing agreement is an agreement by which the party adhered himself to provide acontentment of goods to other party in certain time, with payment of a price afforded by thelatter party. In the cities as the center of government activities, tourism, trade as well aseconomy which led to the growth of diverse businesses and construction of buildings forbusiness place. The building for the place of business must not deviate from the regionalmaster plan and not disturb the environmental preservation. Therefore this paper explainsthe form of the leasing agreement of the store-house between the tenant and the owner. Inaddition, this paper also discusses . The effect of the legal agreement of the store-house(Ruko) made by authentic act and “under hand” act
Keywords: Agreement, Lease, Store-House